(untitled) (Cadernos de Psicologia Social do Trabalho, 2010)
This study discusses the results of a research of the work of women in meat production, with the analysis of their trajectories identity. This analysis is based on the history of women's work in the present and its future projects. The participants of the research were three women who worked in two small slaughterhouses of animals, with rural characteristics. For the purchase of information, interviews were conducted with workers and observations in the field, as well as analysis of documents on the production of meat. The results were organized into three thematic categories: look to the past, between being worker and be the owner of a slaughterhouse and the future professionals. It was possible to identify earlier experiences of the interviewees articulated with the production of meat as food and as a means of subsistence family. It was proven that the daily practices of work were marked by the educational possibilities and restrictions of the interviewees. With respect to the future professional there was prominent in the permanence of workers in the slaughterhouses with aspirations to pursue other activities.